A Comprehensive Review of Affordance Theory in Enhancing Digital Health Solutions - Liu, Zhengyang; Choi, Albert Young (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The interplay between humans and objects is a foundational aspect of visual perception, significantly enriched by Gibson's introduction of Affordance Theory. This theory posits that human interaction with objects is predicated on the recognition of what these objects can provide or afford them. This premise has sparked a vibrant debate within the Information Systems (IS) community, leading to the emergence of two distinct interpretative schools of thought. The first school accentuates the role of user perception and the intrinsic features of IT artifacts in co-creating affordances. In contrast, the second school asserts that affordances are inherently integrated within the IT artifact's design and features.This review critically examines the divergent applications of Affordance Theory by these schools, with a particular emphasis on mHealth app studies. It proposes a comprehensive framework that synthesizes key arguments from both perspectives, aiming to offer researchers a refined tool for leveraging Affordance Theory. Furthermore, this framework seeks to aid designers in enhancing the usability and utility of IT artifacts, thereby bridging theoretical insights with practical application. Through this analysis, the paper endeavors to contribute to a nuanced understanding of Affordance Theory and its implications for digital health solutions.